Analisa Manajemen Risiko Pada UMKM Hijab Menggunakan Matriks Risiko Manajemen : Studi Kasus “Elmillahijab” di Kota Bandung - Nayla Rubayyina Nugraha; Ai Malita Wulandari; Intan Nur’aini; Nuri Triani Anggraeni; Alfiana Alfiana (Indo Publishing, 2026)
This study aims to analyze risk management at the Elmillahijab MSME in Bandung using a risk matrix approach. The method used was descriptive qualitative through direct observation and interviews with the business owner. The results showed that 31 risks were identified and categorized into six main types: market, financial, marketing, operational, human resources, and legal risks. Based on likelihood and impact analysis, 1 risk was identified as very high, 8 as high, 9 as medium, 12 as low, and 1 as very low. The most dominant risks stem from competitors conducting large-scale promotions, increasing raw material prices, and errors in pricing. Recommended risk management measures include regular market research, improving product quality, strengthening digital branding, and diversifying raw material suppliers. This study emphasizes the importance of implementing risk management at the MSME level to increase business resilience, maintain business sustainability, and strengthen competitive position in the ever-growing hijab fashion market.